2006
DOI: 10.1097/01.mib.0000225330.38119.c7
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotics in the treatment of inflammatory bowel disease

Abstract: An increasing amount of evidence suggests that enteric flora may have a role in the pathogenesis of inflammatory bowel disease (IBD). Patients with IBD appear to have an altered composition of luminal bacteria that may provide the stimulus for the chronic inflammation characterizing IBD. The suspected role of bacteria in the pathogenesis of IBD provides the rationale for using agents, such as antibiotics, that alter the intestinal flora. However, there remains much uncertainty about the optimal use of antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 137 publications
(264 reference statements)
3
54
0
2
Order By: Relevance
“…These beneficial effects were associated with reduced iNOS and MMP expression in the intestinal tissue. Supporting these observations, Garrido-Mesa et al (2011a) confirmed the intestinal antiinflammatory effect of minocycline in experimental models of colitis in both mice and rats, showing it to have a higher efficacy than other antibiotics like metronidazole, traditionally used to treat human inflammatory bowel disease, although it was devoid of immunomodulatory properties (Perencevich and Burakoff, 2006). That study proposed that minocycline's ability to modulate both the immune and the microbiological parameters of the disease contribute to its beneficial effects.…”
Section: Effects Of Minocycline On Inflammatory Bowel Diseasesupporting
confidence: 70%
“…These beneficial effects were associated with reduced iNOS and MMP expression in the intestinal tissue. Supporting these observations, Garrido-Mesa et al (2011a) confirmed the intestinal antiinflammatory effect of minocycline in experimental models of colitis in both mice and rats, showing it to have a higher efficacy than other antibiotics like metronidazole, traditionally used to treat human inflammatory bowel disease, although it was devoid of immunomodulatory properties (Perencevich and Burakoff, 2006). That study proposed that minocycline's ability to modulate both the immune and the microbiological parameters of the disease contribute to its beneficial effects.…”
Section: Effects Of Minocycline On Inflammatory Bowel Diseasesupporting
confidence: 70%
“…teria (5,34) and TLR4 antagonist Abs (35), or depletion of TLR4 (36,37) ameliorates colonic inflammation. However, depletion of commensal bacteria or TLR adaptor protein MyD88 also results in profound defects in the ability to repair DSS-induced mucosal damage (32,38).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increasing amount of evidence suggests that intestinal microflora may play a role in IBD pathogenesis. Therefore, antibiotics are generally used in patients with active IBD [21]. In experimental studies, IBD does not develop in murine models of colitis that are raised in a GF environment but occurs when commensal bacteria are introduced into the intestines [6,23,27].…”
Section: Discussionmentioning
confidence: 99%